2021
DOI: 10.3390/ijerph18041527
|View full text |Cite
|
Sign up to set email alerts
|

Access to Nature in a Post Covid-19 World: Opportunities for Green Infrastructure Financing, Distribution and Equitability in Urban Planning

Abstract: Covid-19 changed the way many people viewed and interacted with the natural environment. In the UK, a series of national lockdowns limited the number of places that individuals could use to support their mental and physical health. Parks, gardens, canals and other ”green infrastructure” (GI) resources remained open and were repositioned as “essential infrastructure” supporting well-being. However, the quality, functionality and location of GI in urban areas illustrated a disparity in distribution that meant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 63 publications
(80 reference statements)
3
26
0
Order By: Relevance
“…Consistent with a growing body of other research, our results suggest that investment in green infrastructure is important for supporting young people’s mental health “in place” during lockdowns [ 33 , 70 ]. A UK-based study reported that not having access to a private outdoor space during the pandemic was associated with greater psychological distress [ 20 ], while other studies have highlighted the mental health benefits offered by domestic gardens for both young and older individuals during lockdowns [ 35 , 37 , 71 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with a growing body of other research, our results suggest that investment in green infrastructure is important for supporting young people’s mental health “in place” during lockdowns [ 33 , 70 ]. A UK-based study reported that not having access to a private outdoor space during the pandemic was associated with greater psychological distress [ 20 ], while other studies have highlighted the mental health benefits offered by domestic gardens for both young and older individuals during lockdowns [ 35 , 37 , 71 ].…”
Section: Discussionsupporting
confidence: 89%
“…Mobility and other restrictions at different points during the pandemic have also meant that peoples’ immediate physical surroundings are likely to have greater influence on mental health [ 31 ]. In particular, having access to public urban greenspaces [ 32 , 33 , 34 ] and private outdoor spaces [ 35 , 36 ], living in greener neighbourhoods [ 20 , 37 , 38 ], and having ‘natural’ views from home [ 36 , 37 , 39 ] have been linked with better mental health across a range of populations during the pandemic. Beyond access and incidental exposure to nature, purposive time spent in nature during the COVID-19 pandemic has also been linked with better mental health [ 17 , 20 , 26 , 31 , 34 , 35 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…An ecological study of 135 urbanized U.S. counties found that more countylevel greenspace was associated with lower racial disparities in infection (Lu et al 2021). This finding aligns with earlier evidence of an equigenic impact of greenspace (Mitchell and Popham 2008;Rigolon et al 2021) and supports the value of greenspace as a strategy for health equity in the pandemic recovery (Geary et al 2021;Mell and Whitten 2021).…”
Section: Changing Modes Of Travel?supporting
confidence: 73%
“…Private gardens acted as a safe green space without the risk of being exposed to the coronavirus while maintaining social distancing guidelines (Poortinga et al 2021;Shoari et al, 2020;Pan et al, 2021). This conclusion highlights the potential inequities in nature contact during lockdown because a larger share of the socioeconomically deprived population may not have had private or community gardens (Mell and Whitten, 2021;Natural England, 2020). Implications of our findings on environmental and social justice are further discussed in Section…”
Section: Opportunities For Nature Exposurementioning
confidence: 93%
“…With the increasing risk of future zoonotic pandemics (Quammen, 2012), public health officials, urban planners, and policymakers need to rethink the importance of nature in increasing resilience and adaptive capacity for future emergencies (Mell and Whitten, 2021;Moglia et al, 2021). This review therefore concludes with a discussion of how nature exposure might be considered as a coping mechanism against future pandemics and epidemics to promote public health.…”
Section: Introductionmentioning
confidence: 99%